IDIOPATHIC THROMBOCYTOPENIC PURPURA - Alvina .; Diana Aulia (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Idiopathic thrombocytopenic purpura is an autoimunne disease with low platelet count and bleeding manifestation like purpura, echymosis, petechie, mucosa membrane bleeding. The cause of ITP is platelet coated with specific thrombocyte autoantibody. Idiopathicthrombocytopenic purpura is classified as primary or secondary. The primary ITP is classified as acute and chronic.. Children and adultonset idiopathic thrombocytopenic purpura are different. An Acute ITP can be found in children and chronic onset can be found in adult.The duration of bleeding may help to distinguish acute and chronic idiopathic thrombocytopenic purpura. The diagnosis of idiopathicthrombocytopenic purpura remains one of exclusion after other thrombocytopenic disease are ruled out based on history and needanamnesa, physical examination, thrombocyte count, perifer blood smear examination, bone marrow smear examination. The treatmentis to raise the platelet count into a hemostatically safe range. This article presented a study case of idiopathic thrombocytopenic purpuraon an old woman with DIC which caused her death.